Cardiovascular disease risk perception among community adults in South China: a latent profile analysis - Guo, Zhiting; Yuan, Yong; Fu, Yujia; Cui, Nianqi; Yu, Qunfei; Guo, Erling; Ding, Chuanqi; Zhang, Yuping; Jin, Jingfen (Frontiers in Public Health, 2023)
Objective: Risk perception, a critical psychological construct, influences health behavior modification and maintenance of individuals with cardiovascular disease (CVD) risk. Little is known about CVD risk perception among Chinese adults. This research examined the profiles of CVD risk perception of community adults in South China, and explored the characteristics and factors that influence their perception of CVD risk. Method: This cross-sectional study was conducted in Zhejiang Province from March to July 2022 and included 692 participants. Risk perception was assessed using the Chinese version of Attitude and Beliefs about CVD Risk Questionnaire. Latent profile analysis (LPA) was performed to extract latent classes of risk perception. These classes of risk perception were compared with 10-year CVD risk categories to define correctness of estimation. Chi-square tests and regression analyses were used to identify differences between these categories. Results: Three CVD risk perception classes were identified by LPA: low risk perception (14.2% of participants), moderate risk perception (46.8%), high risk perception (39.0%). Individuals who were aged with 40-60 year (OR = 6.94, 95% CI = 1.86-25.84), diabetes (OR = 6.26, 95% CI = 1.34-29.17), married (OR = 4.52, 95% CI = 2.30-8.90), better subjective health status (OR = 3.23, 95% CI = 1.15-9.10) and perceived benefits and intention to change physical activity (OR = 1.16, 95% CI = 1.05-1.27) were more likely to be in the high-risk perception class. Compared to absolute 10-year CVD risk based on China-PAR, a third of participants (30.1%) correctly estimated their CVD risk, 63.3% overestimated it and 6.6% underestimated it. CVD risk underestimation was associated with hypertension (OR = 3.91, 95% CI = 1.79–8.54), drinking (OR = 3.05, 95% CI = 1.22–7.64), better subjective health status (OR = 2.67, 95% CI = 1.18–6.03). Conclusions: Most adults in South China possess a moderate level of CVD risk perception. Advanced age, higher monthly income, diabetes and better health status were significantly related to higher perceived CVD risk. Individuals with hypertension, drinking and better health status were associated with CVD risk underestimation. Healthcare professionals should pay attention to the indicators for different classes and identify underestimation group as early as possible.